Human Prostate DU145 Carcinoma Cells Implanted in Nude Mice Remove the Peritoneal Mesothelium to Invade and Grow as Carcinomas. Issue 1 (25th October 2012) - Gilloteaux, Jacques; Jamison, James M.; Neal, D.; Arnold, David; Taper, Henryk S.; Summers, Jack L
Abstract Implanted human, androgen‐independent prostatic carcinoma cells (DU145) into athymic (NCr nu/nu) mice produce diverse tumors on the peritoneal surfaces of many organs. Light and ultrastructural observations show that the mesothelial covering these surfaces are typically microvilli‐coated, squamous cells or secretory cuboidal cells. The peritoneal regions colonized by tumors lack mesothelial cells and are covered by actively replicating carcinoma cells that grow as poorly differentiated cell clusters made of cell aggregates to somewhat compact spheroids covered with pleiomorphic microvilli and containing an undifferentiated vascular supply. These xenografts clusters invade the diaphragm and develop into tumors with both a basal solid aspect and an upper region of cribriform morphology. Furthermore, each tumor contains two cell types: (1) a poorly differentiated clear cell type, which grows into intraperitoneal tumors and (2) a large, basophilic cell type, which invades the peritoneal stroma of organs, including of the diaphragm. Anat Rec, 2013. © 2012 Wiley Periodicals, Inc.